2017
DOI: 10.1021/acs.inorgchem.7b02073
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Metalloproteins for Binding and Stabilization of a Semiquinone Radical

Abstract: The interaction of a number of first-row transition-metal ions with a 2,2′-bipyridyl alanine (bpyA) unit incorporated into the lactococcal multidrug resistance regulator (LmrR) scaffold is reported. The composition of the active site is shown to influence binding affinities. In the case of Fe(II), we demonstrate the need of additional ligating residues, in particular those containing carboxylate groups, in the vicinity of the binding site. Moreover, stabilization of di-tert-butylsemiquinone radical (DTB-SQ) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…In an interesting recent development, the Roelfes group described the binding and stabilization of semiquinone radicals (Figure8e) by artificial metalloproteins containing a number of first row metals in the LmrR_M89Bpy-Ala template. [38] Although catalytic functionh as not been demonstrated, this study may provide af irst step towards harnessing the chemistry of unstabler adicals, with potentialf uture applications in catalysis.…”
Section: Artificial Metalloenzymes Containing Metal-chelating Amino Amentioning
confidence: 95%
See 1 more Smart Citation
“…In an interesting recent development, the Roelfes group described the binding and stabilization of semiquinone radicals (Figure8e) by artificial metalloproteins containing a number of first row metals in the LmrR_M89Bpy-Ala template. [38] Although catalytic functionh as not been demonstrated, this study may provide af irst step towards harnessing the chemistry of unstabler adicals, with potentialf uture applications in catalysis.…”
Section: Artificial Metalloenzymes Containing Metal-chelating Amino Amentioning
confidence: 95%
“…Although the catalytic efficiencies of the artificial metalloenzymes created in the LmrR template remain modest, these studies demonstrate that the installation of metal chelating amino acids into proteins can lead to the creation of metalloprotein catalysts for non‐biological, enantioselective transformations. In an interesting recent development, the Roelfes group described the binding and stabilization of semiquinone radicals (Figure e) by artificial metalloproteins containing a number of first row metals in the LmrR_M89Bpy‐Ala template . Although catalytic function has not been demonstrated, this study may provide a first step towards harnessing the chemistry of unstable radicals, with potential future applications in catalysis.…”
Section: Artificial Metalloenzymes Containing Metal‐chelating Amino Amentioning
confidence: 99%
“…It was shown that other divalent first-row transition-metal ions, such asNi(II), Co(II), and Zn(II), are also efficiently bound to BpyA. 36 The corresponding iron protein could also be created, albeit this required the introduction of additional carboxylate moieties in the vicinity of the metal-BpyA site, most likely to act as additional ligands to the iron center.…”
Section: Artificial Metalloenzymes With Covalently Attached Metal Cofmentioning
confidence: 99%
“…(c) EPR spectra of LmrR_M89BpyA with various divalent metal ions and bound DTB-SQ. Reproduced with permission from ref ( 36 ). Copyright 2017 American Chemical Society.…”
Section: Artificial Metalloenzymes With Covalently Attached Metal Cofmentioning
confidence: 99%
“…Metal complexes found in naturally evolved proteins play an important role in the stabilization of the 3D structure and function of proteins. Inspired by these metal complexes, metals and ligands that are not used in naturally evolved proteins have been incorporated into protein and peptide scaffolds to utilize the potency of the formed metal complexes and/or regulate the structure of the scaffolds . For example, Lee et al demonstrated that a copper‐bipyridine complex formed in a DNA binding protein could oxidatively cleave DNA .…”
Section: Introductionmentioning
confidence: 99%